1979
DOI: 10.1104/pp.64.6.924
|View full text |Cite
|
Sign up to set email alerts
|

Glycerolipid and Fatty Acid Changes in Eastern White Pine Chloroplast Lamellae during the Onset of Winter

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…After the thaw, both mCa and freezing tolerance returned to prethaw levels. Sequential changes in mCa and frost tolerance levels, coupled with the well documented changes in membrane structure in leaf tissue of north temperate conifers during cold acclimation (e.g., DeYoe and Brown, 1979;Beck, 1982, 1984), strongly support the contention that mCa is important to cold tolerance and that acid mist alterations of mCa cause membrane destabilization and a concomitant loss in freezing tolerance.…”
Section: Evidence Of Acid-induced Calcium and Cold Tolerance Perturbamentioning
confidence: 70%
“…After the thaw, both mCa and freezing tolerance returned to prethaw levels. Sequential changes in mCa and frost tolerance levels, coupled with the well documented changes in membrane structure in leaf tissue of north temperate conifers during cold acclimation (e.g., DeYoe and Brown, 1979;Beck, 1982, 1984), strongly support the contention that mCa is important to cold tolerance and that acid mist alterations of mCa cause membrane destabilization and a concomitant loss in freezing tolerance.…”
Section: Evidence Of Acid-induced Calcium and Cold Tolerance Perturbamentioning
confidence: 70%
“…Bervaes et al (2) have also observed that hardened pine has a lower MGDG/DGDG ratio than dehardened pine. Such a change would increase the capacity of the polar heads of the galactolipids to bind water, which might be an acclimation of the thylakoids to increase their resistance to freeze dehydration when water freezes extracellularly during the winter (2,4).…”
Section: Discussionmentioning
confidence: 99%
“…The resistance to cold in general greatly depends on the presence of sufficient amounts of unsaturated lipids. A corresponding increase of a-linolenic acid and galactolipids during autumn or winter has been observed in needles of pine (SENSER 1982), Norway spruce (OEQUIST 1982) and Eastern white pine (DEYOE and BROWN 1979). The chances in the fatty acid pattern are accompanied by increased amounts of protein in both the younger and older needles and, in the younger needles, by slightly reduced amounts of chlorophyll b and increased amounts of carotenoids.…”
Section: Discussionmentioning
confidence: 89%